Pengaruh Pengembangan Karir Terhadap Kepuasan Kerja PT. PLN (Persero) Unit Induk Penyaluran dan Pusat Pengatur Beban (UIP3B) SULAWESI - Uhud Darmawan Natsir; A. Ainun Dwi Resky Amalia S; Tenri S.P Dipoatmodjo; Romansyah Sahabuddin; Burhanuddin Burhanuddin (Universitas Veteran Bangun Nusantara, 2025)
This study aims to analyze the influence of career development on the job satisfaction of employees of PT. PLN (Persero) Distribution Main Unit and Load Control Center (UIP3B) SULAWESI. The research method uses a quantitative approach with data collection techniques in the form of observations, interviews, and questionnaires which were distributed to 70 respondents. Data analysis was performed using simple linear regression with the help of SPSS software version 26. The results of the analysis show that career development has a positive and significant influence on employee job satisfaction. With a determination coefficient (R2) value of 2.8%, it identifies that 2.8% variation in job satisfaction is explained by career development implemented by the company. Meanwhile, the remaining 97.2% were influenced by other factors not studied in this study. These findings confirm that a planned and fair career development program can improve job satisfaction, thereby helping companies achieve better organizational performance.